Risk measurement and its role in preparing the target cash flow statement and rationalizing administrative decisions - قصي صفوان; منذر سمر (Journal of Economics and Administrative Sciences, 2018)
Abstract : The Aims of this research is to describe the concept of risk, its type and method of measurement, and to clarify the impact of these risks on the expected cash flow statement and the preparation of the target cash flow statement that takes these risks into consideration. Because the local economic environment is exposed to many risks, Therefore, this list will be predictive, which will help the economic unit to make administrative decisions, especially decisions related to operational, investment and financing activities. Therefore, the research problem is based on the fact that most of the local economic units are the list of flows According to the actual basis and not according to the discretionary basis (budgets) and without taking into account the risks of both types and without activating the role of this list in the decision-making process. The following hypothesis will be tested through this research. (The "Pepsi Baghdad"), as well as companies listed in the industrial sector of the Iraq Stock Exchange and for ten years starting from the date of the report. In 2006 and until the year 2015 and to clarify the impact of risk on the statement of cash flows and their role in guiding decisions through the application of standard financial ratios derived from the statement of cash flows. The study found a number of conclusions, the most important of which is the need to take into account the risks (systemic and irregular) in the process of preparing the list of cash flows, and the application of financial ratios in different dimensions (actual, expected, targeted) Cash Flows. Therefore, the researchers recommend all economic units to use the standard financial ratios as a tool to rationalize administrative decisions, and also to redevelop the process of preparing the list of cash flows and adopt the proposed mechanism to prepare the list of cash flows targeted, taking future risks of both types